Administrative responsibility of the President of Ukraine - Verbitska, Mariana; Deineka, Anna (Actual problems of law (Aktual'ni problemi pravoznavstva), 2023)
The article is devoted to the study of the problem of administrative responsibility.The results of the investigation into the procedure for bringing the President of Ukraine to administrative responsibility are reflected.It was determined that there is no legislative regulation of the process of bringing the head of state to administrative responsibility. In the course of the research, a global problem was identified, namely the absence of the Law of Ukraine «On the President of Ukraine», and it was noted that the issue of administrative responsibility of the head of state would be expedient to be highlighted in this normative legal act. It is proposed to introduce changes and additions to the domestic legislation in order to settle the mentioned issue. The problem was considered taking into account the unprecedented nature of the event of the President of Ukraine committing a misdemeanor. When conducting the research, it was determined the need to maintain a balance between ensuring the equality of everyone before the law and the court, guaranteed by the Constitution of Ukraine, the European Convention on Human Rights, regardless of the position held or any other characteristics and state needs, including regarding the full, timely and proper performance of one᾽s powers and functions of the President of Ukraine.When studying the issue, we encountered the problem of the lack of definition of the legal responsibility of the President of Ukraine and the lack of establishment of the types of such responsibility, the complete lack of a list of sanctions for the head of state. The study is aimed at studying the possibility of bringing the President of Ukraine to administrative responsibility, taking into account the status and inviolability of the head of state. For the sake of objectivity, the concept, essence and scope of presidential immunity are considered. It is clarified for what purpose immunity is granted to the head of the state, attention is focused on the fact that immunity is not a privilege, but a necessity that ensures the correct, quick and effective exercise of his powers by the president.